Accounting principles for non-executive directors - Holgate, Peter, 1953-; Buckley, Elizabeth; Cambridge eBooks (Cambridge : Cambridge University Press, 2009)
Good quality non-executive directors are essential to good corporate governance. They bring a wealth of experience to the boardroom, and together with their fellow board members they are responsible for the company's annual report and accounts. However, very few are trained accountants. This volume explains the key elements of a listed company's annual report and accounts. Part I explains the difference between profit and cash flows, the accounting profession, the international harmonisation of accounting rules, the origins of the rules governing the preparation of accounts, the regulation of financial reporting and the overarching principles behind accounting rules. Part II discusses issues relevant to listed companies: mergers and acquisitions; earnings per share; realised and distributable profits; financial instruments; and other key topics. An appendix sets out 50 questions, linked to the chapters, which non-executive directors might like to ask at meetings of the board and audit committee.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Accounting -- Great Britain; Accounting -- Standards -- Great Britain; Accounting -- Law and legislation -- Great Britain; Electronic books